2022
DOI: 10.3390/biomedicines10020420
|View full text |Cite
|
Sign up to set email alerts
|

Chemokine CCL9 Is Upregulated Early in Chronic Kidney Disease and Counteracts Kidney Inflammation and Fibrosis

Abstract: Inflammation and fibrosis play an important pathophysiological role in chronic kidney disease (CKD), with pro-inflammatory mediators and leukocytes promoting organ damage with subsequent fibrosis. Since chemokines are the main regulators of leukocyte chemotaxis and tissue inflammation, we performed systemic chemokine profiling in early CKD in mice. This revealed (C-C motif) ligands 6 and 9 (CCL6 and CCL9) as the most upregulated chemokines, with significantly higher levels of both chemokines in blood (CCL6: 3–… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…41 As an important chemokine for the recruitment of macrophages, Ccl9 was reported to be involved in various types of inflammatory diseases, such as atherosclerosis, 42 enteritis, 43 and chronic kidney disease. 44 Increased Ccl9 expression has also been observed in rat models of left-ventricular hypertrophy. 45 Here, a total of 9 upregulated lncRNAs were positively correlated with Ccl9, indicating that these lncRNAs may participate in the molecular mechanism of AVMC by mediating Ccl9 action.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…41 As an important chemokine for the recruitment of macrophages, Ccl9 was reported to be involved in various types of inflammatory diseases, such as atherosclerosis, 42 enteritis, 43 and chronic kidney disease. 44 Increased Ccl9 expression has also been observed in rat models of left-ventricular hypertrophy. 45 Here, a total of 9 upregulated lncRNAs were positively correlated with Ccl9, indicating that these lncRNAs may participate in the molecular mechanism of AVMC by mediating Ccl9 action.…”
Section: Discussionmentioning
confidence: 99%
“…Among them, Ccl9 (also called MIP‐1γ), a member of the macrophage inflammatory protein (MIP)‐1 CC chemokine subfamily, was significantly overexpressed in AVMC and regulated by most DElncRNAs 41 . As an important chemokine for the recruitment of macrophages, Ccl9 was reported to be involved in various types of inflammatory diseases, such as atherosclerosis, 42 enteritis, 43 and chronic kidney disease 44 . Increased Ccl9 expression has also been observed in rat models of left‐ventricular hypertrophy 45 .…”
Section: Discussionmentioning
confidence: 99%
“…TLRs, NLRP3, and cGAS-STING pathways produce the upregulation of cytokines, vasoactive substances, chemokines, and inflammatory responses [46][47][48]. Chemokine's overstimulation produces the recruitment of leukocytes to tissues and dysregulated infiltration, leading to chronic cardiac damage [49][50][51]. Interestingly, experimental studies have shown that chemokines are upregulated in the heart during CKD, establishing a link for CRS type 4 development [52,53].…”
Section: The Kidney-heart Crosstalkmentioning
confidence: 99%